TEACHER CREATIVITY REVIEWED FROM WORK ENVIRONMENT PRINCIPAL LEADERSHIP AND WORK MOTIVATION AT SMA BATIK 2 SURAKARTA - Hadiyati, Salamah; Mursito, Bambang; Aryati, Ida; Probowati, Anna (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to see the effect simultaneously or partially the variables of the work environment,principal’s leadership and work motivation with the creativity of teachers at SMA Batik 2 Surakarta. Researchers conducted observations at SMA Batik 2 Surakarta with the object of teacher research as a sample in order to determine the relationship between of the work environment,principal’s leadership and work motivation with the creativity. The research method is in the form of survey research using quantitative research with a sample size of about 49 teachers. The data collection method used a questionnaire with a saturated sampling technique. Processing of data using the SPSS program using multiple regression equation analysis tools, F test, t test, and the coefficient of determination. The results of the analysis can be obtained that the variables of the work environment,principal’s leadership and work motivation with the creativity have a simultaneous effect on the teachers SMA Batik 2 Surakarta. the work environment has a significant effect on the creativity of teachers in SMA Batik 2 Surakarta. principal’s leadership ability has a significant effect on the teachers of the creativity SMA Batik 2 Surakarta. Leadership style has a significant effect on the teachers the creativity of SMA Batik 2 Surakarta. Work motivation has a significant effect o the creativity of teachers at SMA Batik 2 Surakarta. The results of the observation show that simultaneously the independent variables which include of the work environment,principal’s leadership and work motivation with the creativity of teachers. Keywords: work environment, work motivation , principal’s leadership and with creativity of Teacher Work Productivity